Chapter Guerra e pace nell'europeismo federalista di Bruno Trentin - Cantaro, Antonio (Studi e saggi, 2023)
The essay dwells on the important reflection on the dialectic between war and peace that Trentin opens up in parallel with the first and second Gulf Wars, involving the role of the Union as an international actor and the need for European defense before the waning of American hegemony. The author points out how Trentin participates in the life of the European Parliament with the same intellectual setting that led him heretically to argue that "freedom comes first". Political Europe comes first, he argued. The importance of a political Europe in the governance of globalization is, in fact, central to his tenure in the European Parliament and his battle for the approval of the European Constitution project.